Rút gọn biểu thức
1) \(\sqrt{6\sqrt{2}+11}\) - \(\sqrt{11-6\sqrt{2}}\)
2) (\(\sqrt{3}\) - 2)\(\sqrt{7+4\sqrt{3}}\)
Rút gọn biểu thức sau:
\(\sqrt{11}-6\sqrt{2}+\sqrt{3}-2\sqrt{2}\)
Rút gọn các biểu thức :
A/ √3-2√2 +√9+4√2
B/ √8-2√7 - √8+2√7
C/ √11+6√2 - √11-6√2
Giúp em với ạ, em đang cần gấp.
rút gọn biểu thức
căn 11+6 căn 2
Rút gọn biểu thức :
\(\sqrt{\dfrac{5}{2}-\sqrt{6}}-\sqrt{\dfrac{11}{2}-2\sqrt{6}}\)
Rút gọn các biểu thức:
M = 3 − 2 2 − 6 + 4 2 N = 2 + 3 + 2 − 3
Rút gọn các biểu thức:
M = 3 − 2 2 − 6 + 4 2 N = 2 + 3 + 2 − 3
Rút gọn các biểu thức:
M=√3−2√2−√6+4√2M=3−22−6+42
N=√2+√3+√2−√3
Thực hiện phép tính (rút gọn biểu thức)
a) \(\sqrt{9+4\sqrt{5}}\) - \(\sqrt{9-4\sqrt{5}}\)
b) \(\sqrt{12-6\sqrt{3}}\) + \(\sqrt{12+6\sqrt{3}}\)
c) \(\sqrt{6\sqrt{2}+11}\) - \(\sqrt{11-6\sqrt{2}}\)